Short-term effect of a synbiotic in salivary viscosity and buffering capacity; a quasi-experimental study. - Yolanda Hernández; Briana Medina; Edith Mendoza; Luis Octavio Sánchez-Vargas; Diana Alvarado; Saray Aranda-Romo (Universidad de Concepción., 2020)
Evaluate the effect of a synbiotic on salivary viscosity and buffer capacity. Materials and Methods: A follow-up one-week study was performed on 24 healthy volunteers in San Luis Potosí, Mexico, during July 2017. Volunteers must have had active tooth decay at the moment of study. All 24 patients were given a Lactiv® probiotic package, advising not to modify usual oral hygiene practices, and were followed up during 6 days. Primary output variable was salivary viscosity while the secondary was salivary buffer capacity. Salivary viscosity was assessed by using an Ostwald Pipette and buffer capacity with bromocresol purple. Results: A total of 8 male patients (33.3%) and 16 females (66.6%) patients were included, with an average age of 10.92 years. All the volunteers completed the study. Comparisons between pre- and post-treatment showed a decrease in salivary viscosity, while buffer capacity was showed to increase. Conclusion: The use of a synbiotic during a short period of time lowered the viscosity of saliva and increased salivary buffer capacity.